The relationship of vascular glycolipid storage to clinical manifestations of Fabry disease - Gupta, Surya N.; Ries, Markus; Kotsopoulos, Steven; Schiffmann, Raphael (Medicine, 2005)
Abstract:Fabry disease is a rare X-linked lysosomal storage disorder caused by deficient activity of α-galactosidase A (α-Gal A) resulting in the storage of glycosphingolipids, especially globotriaosylceramide (Gb3), in cells throughout the body, causing life-threatening renal, cardiac, and cerebrov
Gesehen am 16.05.2019